Cannabinoid Receptor 1/miR-30b-5p Axis Governs Macrophage NLRP3 Expression and Inflammasome Activation in Liver Inflammatory Disease - Le Yang; Lei Tian; Zhi Zhang; Xuan Zhou; Xiaofang Ji; Fuquan Liu; Chengbin Dong; Lei Hou; Xinhao Zhao; Na Chang; Lin Yang; Liying Li (Elsevier, 2020)
Nod-like receptor (NLR) family pyrin domain containing 3 (NLRP3) has been regarded as an important initiator or promoter in multiple inflammatory diseases. However, the relationship between cannabinoid receptor 1 (CB1) and macrophage NLRP3 inflammasome and the corresponding molecular mechanism in liver inflammation remain unclear. Mouse liver injury models were induced by carbon tetrachloride (CCl4) or methionine-choline-deficient and high fat (MCDHF) diet. Human liver tissues were obtained from patients with different chronic liver diseases. CB1 expression was increased in liver tissue and macrophages of CCl4- and MCDHF-treated mice, positively correlated with NLRP3. CB1 agonist ACEA (Arachiodonyl-2'-Chloroethylamide) promoted NLRP3 expression and NLRP3 inflammasome activation in macrophages. CB1 blockade with its antagonist AM281 reduced NLRP3 expression, inflammasome activation, and liver inflammation in CCl4- and MCDHF-treated mice. MicroRNA-30b-5p (miR-30b-5p), screened by the intersection of bioinformatics databases and downregulated miRNAs in injured liver, negatively correlated with NLRP3 in mouse and human liver. miR-30b-5p was involved in CB1-mediated activation of NLRP3 inflammasome in macrophages by directly targeting NLRP3. Importantly, administration of miR-30b-5p agomir targeted NLRP3 and attenuated liver inflammation in the injured liver. Altogether, CB1/miR-30b-5p axis modulates NLRP3 expression and NLPR3 inflammasome activation in macrophages during liver inflammation, which provides a potential target for liver disease.